SIGNS, DENOTING ACTIONS AND PROCESSES IN THE PANDEMIC DISCOURSE (on the Material of English Publications, devoted to the Coronovirus Epidemic) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-2-54-62Language signs, denoting actions and processes, are considered on the material of English publications, devoted to the coronavirus epidemic and constituting the pandemic discourse. Represented by verbs and verbal word combinations they are divided into simple and complex units. Besides, they can interact with other signs in the utterance, namely, with the sings, indicating the participants of the situation with the pandemic and the resources, used to fight against it. The results of the research show that in the pandemic discourse these signs name activities, which relate to diagnosing and registering the cases of infection and death, developing new methods of treatment, detection and prevention, controlling the epidemiological situation and imposing security measures, as well as people’s existence during the pandemic, self-isolation and social distancing, the spreading of epidemic and its impact on human health and economy. The semantic variability and functional potential enable these signs not only to inform the readership, but also influence the recipients of the information and shape their opinion on the situation which makes these signs the powerful means of persuasion. Thus, the language signs, which denote actions and processes, play the significant role in the pandemic discourse of English media, being one of its main constituent features.Key words: pandemic discourse, language signs, semiotics, speech persuasion, signs, denoting actions and processes